Personal Data Theft in the Era of Information Technology Progress: Impact and Overcoming Strategies in Indonesia - Dewi, Sumartini; Samara, Muchlas Rastra; Sri D, Pratiwi Ayu (UNTAG Law Review, 2024)
This article examines the problem of information security crimes in the conditions of technological progress with the globalization of international life, including relations between countries, taking into account the high level of development of technological and information resources. The importance of ensuring information security as an object of legal protection protected by written international and national law. This research method is normative with a statutory, historical and philosophical approach. efforts to improve international and national legal policies to modernize the national legal system for the prevention and eradication of cybercrime. An effective legal regulatory mechanism for objects to be legally protected is essential to ensure information security. Special attention is focused on solving the problem of detection, disclosure and accurate legal evaluation of crimes and violations committed in cyberspace. Administrative instruments, institutions, international cooperation, community participation, dispute resolution and procedural law, prohibitions on the use of personal data and criminal law asLast Remedyto overcome personal data leaks, protect personal data in the process of processing Personal Data in order to guarantee people's constitutional rights.